Proteomic exploration of protein-RNA interactions in human cells - Trendel, Jakob (2019)
The interactions of proteins with RNA are ubiquitous in human cell biology and fundamental to most if not all of life as we know it. Proteins and RNA interact for the purpose of gene expression, where genetic information is encoded within RNA, which serves as template for protein in messenger RNA, as scaffold for the trimming of other RNA within the spliceosome, as a catalyst for the production of protein within the ribosome, and as component of various other processes, many of which we are only beginning to understand. Central to our understanding of such processes is the interplay between proteins and RNA. Protein-RNA interactions are often disrupted by conventional extraction methods and need to be stabilized through crosslinking in order to be appreciated by transcriptomic or proteomic methodology. Crosslinking typically occurs through UV irradiation, which covalently connects protein bound to RNA. However, currently there is no universal method for the extraction of proteincrosslinked RNA available, so that insights can only be gained for certain subsets of the transcriptome or individual RNA-binding proteins, respectively. In this thesis a new method for the extraction of protein-crosslinked RNA from UV-crosslinked cells is described. In order to demonstrate the comprehensive usefulness of the approach, which was termed XRNAX, it is applied for the resolution of several proteomic and transcriptomic problems. First, XRNAX is employed for the purification of ribonucleotide-crosslinked peptides identifying known and unknown protein-RNA interfaces. Next, a comprehensive draft for the human RNA-binding proteome is derived applying XRNAX to three commonly used cell lines. The same approach is applied for the differential quantification of RNA-binding during a timeline of arseniteinduced translational arrest in human cells. Additionally, XRNAX is combined with CLIPseq to monitor the RNA exosome component EXOSC2 processing pre-ribosomal RNA during arsenite stress. At last, XRNAX is used along with TMT-SILAC in order to derive protein half-lives of the human RNA-bound proteome. Half-lives of the RNA-bound proteome are found on average 1.75 fold increased in comparison to the total proteome. For validating the stabilization of protein-RNA complexes, ribosomal assemblies are purified from human cells using polysome profiling and protein half-lives assessed with TMT-SILAC. Stabilization is confirmed, however, only for ribosomal proteins in 80S ribosomes within the 80S or polysome fractions. Further experiments interfering with ribosome biogenesis, the proteasome and autophagy are distilled into a model for the turnover of ribosomal proteins and ribosomal assemblies. In summary, this thesis describes new methodology and biological insight on protein-RNA interactions in human cells.
Keywords: Hochschulschrift